Curse of the thirteenth Fey : the true tale of Sleeping Beauty - Yolen, Jane (Penguin Group (USA), 2013)
Gorse is the thirteenth and youngest in a family of fairies tied to the evil king's land and made to do his bidding. When accident-prone Gorse falls ill just as the family is bid to bless the new princess, a fairytale starts to unfold. Sick as she is, Gorse races to the castle with the last piece of magic the family has left;a piece of the Thread of Life.